Digital Javanese Script Literacy for Cultural Tourism Communication - Yenni Sri Utami; Ida Wiendijarti; Oliver Samuel Simanjuntak (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Bantul Regency promotes cultural tourism through the